2009
DOI: 10.1159/000227783
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Intravitreal Bevacizumab (Avastin) versus Ranibizumab (Lucentis) in the Treatment of Neovascular Age-Related Macular Degeneration

Abstract: Aims: To compare the safety and efficacy of 2 anti-vascular-endothelial-growth-factor agents – bevacizumab (Avastin) versus ranibizumab (Lucentis) – in the treatment of patients with neovascular age-related macular degeneration (AMD). Methods: Retrospective analysis of patients who received intravitreal injections of bevacizumab or ranibizumab for neovascular AMD. Primary outcome measures were best-corrected visual acuity (BCVA) and central foveal thickness (CFT) assessed by Spectral Domain scanning laser opht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 39 publications
2
35
0
2
Order By: Relevance
“…Although there are no wellknown trials with bevacizumab, recent studies have shown that the clinical outcomes of intravitreal bevacizumab injections are similar to those of well-conducted trials of intravitreal ranibizumab injections in neovascular AMD. [10][11][12] In this regard, we have been treating patients with intravitreal bevacizumab injections based on the OCT-guided variabledosing regimen protocol suggested by the PrONTO study. However, clinical results in our patients have been quite different to those reported in either the MARINA or the ANCHOR trials.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no wellknown trials with bevacizumab, recent studies have shown that the clinical outcomes of intravitreal bevacizumab injections are similar to those of well-conducted trials of intravitreal ranibizumab injections in neovascular AMD. [10][11][12] In this regard, we have been treating patients with intravitreal bevacizumab injections based on the OCT-guided variabledosing regimen protocol suggested by the PrONTO study. However, clinical results in our patients have been quite different to those reported in either the MARINA or the ANCHOR trials.…”
Section: Discussionmentioning
confidence: 99%
“…2 Although the use of intravitreal bevacizumab (IVB) for ocular disease did not go through the Food and Drug Administration approval process, published reports suggest that it is safe and apparently effective at treating wet age-related macular degeneration. 3,4 Despite the apparent safety profile of both IVB and ranibizumab, there have been recent reports of elevated intraocular pressure (IOP) after single or multiple injections of either agent. [5][6][7][8] The number of reported cases of IOP spikes has, overwhelmingly, involved IVB prepared in plastic syringes by one or more repackaging formularies with fewer cases involving ranibizumab obtained directly from the manufacturer.…”
mentioning
confidence: 99%
“…Mean initial IOP was 14.2 ± 2.4 mmHg (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), and mean final IOP was 14.3 ± 2.45 mmHg (10-22) (P = 0.94, one-way ANOVA). Four eyes (2 with juxtafoveal CNV and 2 with subfoveal CNV), acquired either glaucoma or ocular hypertension, with an IOP between 22 mmHg and 28 mmHg at diagnosis (mean …”
Section: Intraocular Pressure and Glaucomamentioning
confidence: 93%